1537. Incidence, Reinfection, and Discrepancy Between Site Positivity and Reported Sexual Practice of Sexually Transmitted Infections in HIV-Positive Adolescents and Young Adults in Atlanta, GA. (31st December 2020) - Loerinc, Leah; Scheel, Amy; Jordan-Thompson, Sierra L; Gillespie, Scott; Camacho-Gonzalez, Andres
Abstract: Background: HIV-positive adolescents and young adults (AYAs) are disproportionately affected by sexually transmitted infections (STIs). Despite national recommendations, STI screening remains low. Incomplete screening in addition to inconsistent reported sexual practices may lead to missed infections. This study aimed to determine the incidence and reinfection rates of co-STIs in HIV-positive AYAs and the discrepancy between site positivity and self-reported sexual history in this group. Methods: Retrospective chart review was conducted for all patients aged 13-24 at Grady Ponce and Family Youth Clinic in Atlanta, GA from 2009-2018. Data were collected on demographics and STI events. STIs included gonorrhea (GC), chlamydia (CT), human papillomavirus (HPV), syphilis, trichomonas, herpes simplex virus (HSV), lymphogranuloma venereum (LGV), hepatitis C (HCV), bacterial vaginosis (BV), and chancroid. First STI incidence and incidence of reinfections were calculated by dividing new cases over corresponding person follow-up time. Results: 621 sexually active HIV-positive AYAs were included. The mean age at first observation was 18.7 (±3.29) years. 72.1% of patients were male, 92.3% were Black, and 79.7% were horizontally infected. 83.7% of patients had at least one STI during the study period. The overall first STI incidence rate was 35.8 per 100 person-years with HPV, GC, CT, and syphilis as the most common STIs reported (Table 1). The overall recurrent incidence rate was 72.1 per 100 person-years with GC, CT, and syphilis as the most common recurrent infections (Table 1). Of all GC and CT infections, the majority were rectal (48.7% and 49.9%, respectively) (Table 2). Only 65.8% of patients with rectal GC and 68.5% with rectal CT infections reported recent receptive anal sex (Table 3). Table 1: First and recurrent incidence rates of any STI and individual STIs per 100 person-years Table 2: STIs by site, all infections Table 3: Reported exposure history vs. STI site positivity Conclusion: Our study demonstrates disproportionately high incidence and reinfection rates of co-STIs in HIV-positive AYAs. Furthermore, many patients did not report exposure at their site of infection. If screening is done based off reported exposure history alone, many infections may be missed. Our data support the urgent need for increased STI screening in this population, including routine extragenital testing for GC and CT even without reported exposure at these sites. Disclosures: All Authors : No reported disclosures